PERUBAHAN KURIKULUM DI INDONESIA : STUDI KRITIS TENTANG UPAYA MENEMUKAN KURIKULUM PENDIDIKAN ISLAM YANG IDEAL - Muhammedi Muhammedi (Universitas Islam Negeri Sumatera Utara, 2016)
Indonesia has frequent changes of the curriculum, including curriculumin in 1947, 1964, 1968, 1973, 1975, 1984, 1994, 1997, 2004, 2006, and 2013. Last future education needs to be designed in order to answer the expectations and challenges of the changes that occur , The education system needs to be built continuously from preschool education, elementary education, secondary education and higher education. Islamic education curriculum must meet the elements of monotheism, religious, development of human potential as the vicegerent of Allah, the development of human relations, and the development of ourselves as individuals. As well as the principles in formulating the curriculum of Islamic education, the principle of perfect linkage with religion, including the teachings and values, inclusive (universal)